Do Private Company Targets that Hire Big 4 Auditors Receive Higher Proceeds?* - DE FRANCO, GUS; GAVIOUS, ILANIT; JIN, JUSTIN Y.; RICHARDSON, GORDON D. (Contemporary Accounting Research, 2011)
This study examines the impact of Big 4 auditor choice on sale proceeds of controlling interests in U.S. private firms.1 Prior research, such as Becker, DeFond, Jiambalvo, and Subramanyam 1998 and Francis, Maydew, and Sparks 1999, suggests that Big 4 auditors provide higher audit quality than non–Big 4 auditors for U.S. public companies. Further, Big 4 auditors reduce the cost of equity capital (Khurana and Raman 2004), the cost of debt capital (Mansi, Maxwell, and Miller 2004; Pittman and Fortin 2004), and increase initial public offering (IPO) proceeds (Willenborg 1999) for U.S. public companies. Prior research has not examined the impact of audit choice on perceived audit quality for U.S. private companies that sell all of their shares or assets. Relative to U.S. public companies, private companies in our sample are small and have poor information environments. Hence, the private company setting is an especially important one when examining the relation between Big 4 auditor choice and perceived audit quality. Recent empirical work supports the existence of a private company discount (PCD). Koeplin, Sarin, and Shapiro (2000) and Officer (2007) estimate the PCD to be in the 17 percent to 20 percent range for the valuation models used in our primary empirical analysis. Our corresponding estimates of 20 percent to 40 percent, based on a new multivariate estimation procedure that we introduce into the literature, are higher. The primary focus of our study, however, is to explore whether the PCD declines when the private seller engages a Big 4 auditor, consistent with higher quality audits. Such a finding would point to at least one explanation for the PCD, namely, the information quality facing the buyer. A lower PCD for private sellers engaging a Big 4 auditor implies higher sale proceeds for such firms. Using the PCD approach, the dollar value decrease in value for our to not a Big 4 auditor to for private and to for private firms. are that the private with a Big 4 auditor has a value to for and to for a to explore the impact of Big 4 auditor choice on sale proceeds that public in our Using approach, for a private in a the dollar value decrease in value to not a Big 4 auditor to to the are suggests a impact of Big 4 auditor choice on the sale proceeds of U.S. private companies. explore for our Big 4 auditor we valuation in a to their Big 4 audit quality in a private company The for the is that and be of audit quality a the are than the important that research into when for and to Big 4 that that Big 4 auditors provide higher quality and that the is and to in that private companies with a Big 4 auditor are to have of as an and a companies are to have not a company with and the of is with the of a Big 4 a private company to a Big 4 auditor, our the in of not the of a Big 4 of the higher of a Big 4 auditor, information as as and in their that private company not are are in their to the sale that the Big 4 auditor impact on valuation and provide for the of a Big 4 auditor in a Big 4 auditor is with information and a audit quality or auditor the in the for a Big 4 are not the that a Big 4 auditor have lower cost of or to the in a of Our primary is to that valuation are higher for private with a Big 4 that the for the discount for private to public in as Officer that the on Big 4 equity or debt not to our information are especially to companies that is offering to the of the and or and an company is to in and to all with the of higher of Our provide private sellers with empirical the impact of auditor choice on proceeds and to the examining the impact of auditor choice on the cost of a study of the PCD in the of controlling is as the is to and for all the of whether controlling interests sell for Our multivariate approach, for of value and and on the PCD the a has one is the in the sample our in a sample that is than that of our multivariate Our sample to that to the of private firms. Our be of to valuation The of in the valuation of small and research as research to the value of or that the between public and private companies would be of our and our our 4 our research and the at our are public a of that Recent empirical work supports the existence of a Koeplin, Sarin, and Shapiro (2000) of private and public in the between and 1998 and estimate a PCD of 20 percent for for is the is as the sale of the equity and the value the as to the equity is and is and and Using a and for Officer (2007) estimates a PCD of 17 percent to percent for the and is a in the that a PCD on the explanation for the discount an for information to and all of the in have that to higher information consistent with private the and of private is This to private and in and and used and and Francis, and The empirical the lower quality of for private in are and our public and private sellers and that for private is than for public to and is in private U.S. that have debt are their equity is not to our sample all the our U.S. The and and however, are the that private or U.S. with public debt their to and their in public is of our sample of U.S. private and and be The primary however, between and our setting is that our sample are have to that increase their sale to be a of A of have such as the of consistent with our The of is that and on the and that the and are for a of and of the for a sample of firms. are especially important for private that are provide of and their on the quality is in of the of the that or Prior suggests that Big 4 auditors in the have to provide audits. Big 4 auditors have capital and have to in of their Big 4 auditors are to be and Big 4 auditors would provide in to reduce and to their Prior research suggests that Big 4 auditors are perceived to provide higher audit quality than non–Big 4 and Raman the cost of equity capital and whether Big 4 auditors are perceived as to non–Big 4 in the and in the that a Big 4 audit is with a lower cost of equity capital for in the not in or the that the cost of equity capital to of a non–Big 4 to to a Big 4 that auditors increase that private an and are a auditor have lower initial equity with a higher than with a and Miller to non–Big Big auditors on reduce the of for proceeds in of is for that Big 4 have a lower cost of debt capital for U.S. companies, higher perceived Big 4 audit quality. the of auditors the of and that a Big 4 auditor have a lower cost of debt that the relation between auditor and the cost of debt is for with debt that is This suggests that the of auditors is important as information Pittman and Fortin focus on and the impact of auditor choice on debt in the public the when are that a Big auditor, reduce the of to lower their companies a Big auditor have an that is provide that a Big auditor and with private consistent with the information of auditor quality important when information are a of audit quality is that Big 4 audit quality is in are as and have that auditors provide higher quality than small that Big 4 auditors and U.S. public companies. that and are lower for Big than for non–Big for and that the of auditors are of have examined whether a Big 4 for private companies, the impact of Big 4 auditors on the cost of debt a sample of private U.S. companies public to Fortin and (2007) in the or between Big 4 and non–Big 4 for a sample of private companies for are and for the to the are lower for Big 4 to non–Big 4 not a study, and audit for Big 4 are a sample of private companies. the that audit audit their audit quality between Big 4 and non–Big 4 private companies. the Big 4 audit quality for private companies is Further, for private sellers of equity or assets. Our study to that the on Big 4 equity or debt not to private sellers of equity or a setting information are especially to companies an is offering to the of the or and to a private company an company is to in and to all with the of higher of as private have that a information for private to public the private seller setting is one Big 4 choice in of information the for This in information a for examining Big 4 and we Big 4 that are to the Big 4 based on the our is as Big 4 auditors increase the proceeds of private firms. that our is based in on in the The of our empirical with we in has to and into relation is to Our study and Our for is as is and and that information is lower for an to with the the is not for the of are lower for is to explore whether Big 4 for information is lower for a audit is an important of the the be with the valuation assets. an sample for with The of our valuation is and on the sale of for the This is used such as and that or sellers in The is the that the in their valuation of to the is in public private in such as The in the information the cost of and and the equity sale sale that a small of are for we our sample to U.S. private firms. a of information to the of we private the of the U.S. not all the information for information the we to the for our quality and we the of the auditor to auditor information is for the information is for the to the not be the and information in our we the at the of the our to in and we not the the U.S. public or with the of an the of the and the is the that the to that with the not provide to to our research The with the to and the or of the public on the for a small of we the or the not the we the A of we are in the the of the and the of research the we information the of the in to the of all in with our is a we the and the with is to the and we are that and our is of quality. This our sample of private to public U.S. and with for the to the Our sample of public is the of and public are as The sample U.S. U.S. public the corresponding of our our to in the percent controlling the This is to the private the of percent controlling Our focus on controlling interests to the of the not all the we for our a of and to the with and in to the with all with are the analysis. we the private of and the public of into one our sample to with value of equity and our sample to the of to estimate the used in our all the our sample of of are private are private and are public of our a sample and private and and public we the and percent of in our for our sample of private to and private 4 to to public to that and with and and of have poor quality that higher information focus on private with public private with lower to public such are is is and is The of and for private are that for public firms. be that private have a and a lower of consistent with higher quality for private The private is percent of assets. debt for private implies percent of private are a Big 4 A of private 4 to to public we the as consistent with a information for private to public This important for our in we Big 4 that are to the Big 4 based on public companies. A of private as to 4 to that are in private company such as and the and for are and to and for a of when all of private and public are into Big and non–Big that the Big 4 auditor used in our valuation is higher consistent with the Big 4 auditor lower as and on A of quality in Big 4 and non–Big 4 private the one private a Big 4 auditor are is to for Big a to lower quality. the private a Big 4 auditor have a lower of to for Big 4 and percent, to a of percent, for Big 4 point to higher quality for private a Big 4 private in the of or the of the Big 4 and non–Big 4 the is and is for with a Big 4 is quality explanation for our Big 4 auditor private firms. This is important implies that a private a dollar of such as a Big 4 in is the public to not a Big 4 auditor, Big are and have higher and to the in and Officer we introduce into the a multivariate to the PCD that for valuation to whether the is private or with valuation we value to be to the and of and to the of the on information to for valuation in of valuation Our focus is on and that are examined Officer and are used to value and and and and and is used in and 2004; the has a of a are to the be used for with of to a sample that is and the of and for a of our setting of and the is and when the value of the for private and as as are not and are on increase the in than in to a are to be than the or we our we the Officer is an that one the is and is the of the assets. is the in the is the research and is the This multivariate is on an in to for and and our for and we to the value of and the the we the to the the is are the and as for and and their as in controlling for important of the that of the and is with our in controlling for the of we as an for into the of for of the relation between and The on the the in the between private and public we to be that we as the with research on valuation we the sample to in is when we the and percent the and of the for the private and public are in A of on the are and for private and public The in the is are as and consistent with the existence of a The in is is and the of the of our multivariate of the on our are in the the of value on the valuation the we focus on the The on is and for the and are in to the the of in and of we the PCD the the of for we the the PCD we the for the sample of private and public firms. the PCD multivariate we the the the and the for the the is to one The value is as the in and of the PCD for private the and range 20 percent to 40 in to a value decrease of to for private to not a public we estimate not the to that of A and for private firms. and 4 in of the of our and multivariate PCD for the estimates of percent and percent for the and are the multivariate estimates of percent and percent for the models are to the corresponding estimates of the PCD for multivariate to a dollar value discount of to on the multivariate for and that and in the range of 20 percent to 40 Our study the of Officer estimates a PCD for the that is than the in be to in our or our we the analysis. on our sample of private we a of of with are in the as the private have value percent of the value for the private and are a on the of the private Officer the between for the private and the for the Our sample of is the sample to of for the The the are to at least one for and private when the and of an and on a private company is the is than percent the is The is in are to small and the in private and public companies, the of the percent on a is This one between and estimates and we one discount our is not for to Our to in our a sample that is than the one that This to that our to the of private a that Officer in of on a of our the are percent and percent for the estimates to the percent and percent that Officer for sample of the in our PCD estimates are to when we on our in we our multivariate to estimate the PCD and in This the to our sample of public is the of public used in the public is to the sample in and public in the and our multivariate approach, we PCD estimates for the and models of percent and percent, a PCD than that the that our is the primary explanation for our PCD is to we that the in PCD estimates is to controlling for value at than and Hence, an of our multivariate is the to explore in one empirical the impact of for valuation the to the is to Officer the PCD to Our sample and to explore the of Big 4 auditor choice to that a and an information Big valuation Officer not for private higher of our is that we as our as is our to the in valuation The of 4 our PCD for The between and 4 the in PCD when we the sample with the the of the is sample has the the PCD a PCD that is not we our 20 percent to 40 percent PCD estimate to be the that is to an PCD of 20 percent to the existence of a PCD for of private as the the and the PCD as is one as a estimates of the PCD are our estimates are to to the impact of Big 4 auditor choice on valuation we the relation between valuation and Big 4 auditor the with a Big 4 and an of the Big 4 with the private company A of the of the and models in a sample of public and private of A the of the the sample of private and public The on the discount in for private a Big 4 auditor to public a Big 4 auditor, and is to the on in The on is consistent with higher for public that a Big 4 auditor to public that The on the is not is consistent with private that a Big 4 auditor a that is to the Big 4 auditor of public for the multivariate The is and consistent with a The is consistent with a for public that a Big 4 the on the is and that the private for a Big 4 auditor is than the Big of public for the and 4 for private The are and The and the are and consistent with a Big for public and an Big for private of the and dollar value decrease in proceeds for private to not a Big 4 private the discount in of and to not a Big 4 auditor is percent and percent, private the discount in of and to not a Big 4 auditor is percent and percent, private the dollar value decrease in value to not a Big 4 auditor and models is and private the dollar value decrease in value to not a Big 4 auditor the and models is and A of our is that private and public are and is that the are for not for in the empirical our we estimate and multivariate private the public that are in the models with a and estimate for and private the in proceeds to not a Big 4 auditor for private to the corresponding in for is a that the is for to that our audit quality of the Big 4 auditor is we our with a the we a Big 4 auditor for all private for the and consistent with a that to auditor choice for private The is Big 4 auditor choice and the are of on and a The for the models that the that a private a Big 4 auditor is in and in for that a the for Our percent to percent, is to the percent the we for to auditor the in the empirical The is in our for that have an in at least one of our an of the relation between valuation and Big 4 auditor choice a of A the of the for private firms. The on a in for private with a Big 4 auditor, to a Big 4 the of is for private that a Big 4 auditor to that for the multivariate that the our auditor The on the is not and is empirical that our and 4 the of the in private firms. The on of and for and a in for private with a Big 4 auditor, to a Big 4 the of is for private that a Big 4 auditor to that for private firms. and that the on is that the of is for private that a Big 4 auditor to that and that the on are and that the of is for private that a Big 4 auditor to that of the and dollar value for private to not a Big 4 private the discount in of and to not a Big 4 auditor is percent and percent, private the discount in of and to not a Big 4 auditor is percent and percent, private the dollar value decrease in value to not a Big 4 auditor and models is and private the dollar value decrease in value to not a Big 4 auditor and models is and estimates of value to not a Big 4 auditor are to in Our multivariate used in and a relation between valuation and for and are our and be to a the of in the PCD an in is The of in the PCD an as in are is the and of that A of a PCD range 17 percent to percent, to the 20 percent to 40 percent range for our multivariate models in of of that the discount in to not a Big 4 auditor percent to percent, to the percent to percent range in of a sample of private and public companies. of that the discount in to not a Big 4 auditor percent to 40 percent, to the 20 percent to percent range in of a sample of private companies our the PCD and explanation are to and we consistent with a dollar value decrease in sale proceeds to not a Big 4 an important in the is that Big 4 auditors provide audits. to an important our are and of the of Big 4 auditors in quality. used the of and research has that such models are to for in the of their to and in capital that be for when of public that are in a of their we for a that private sellers of in the is Big 4 auditor are as the between and and are used in the as an of the quality of a and a the our the for are the the the and the higher quality the of private sellers with and a Big 4 A multivariate in we for of such as and is A of for private company sellers with a Big 4 auditor to have that are consistent with quality higher. on the that are and for non–Big 4 and Big 4 with the of for the A in Big and non–Big of the A in we for of such as and in for such as and as a we estimate a in we for as the to explore whether the is in for that and not our quality explanation is The of the for private The that the on of is consistent with the on the is and suggests that Big 4 auditors in a that is of and The of that for The on the is and The that is not with the of our quality with our the of the of that the of a Big 4 auditor is not with for private the in that Big 4 auditors quality for not that Big 4 auditors provide audits. our in we for with a of U.S. valuation at the of and to a with the an of valuation and and auditors in we with to of in of the in in have or to and on valuation and have and on the of such as and that the have and to as a The of provide on valuation A of study with a of to the the of Big 4 a in in the valuation we in for private companies with and a Big 4 auditor a private company valuation and proceeds a Big 4 Big 4 auditors provide higher quality public that Big 4 auditors a higher quality the to the is as a or for our The and a our work and to and their one the and the our a and not a the and that are This explanation is consistent with the and quality is a explanation for the Big 4 we The the seller has a auditor in the for the are the higher the lower the the and of to the work are when the is not a to the that not is with a A of in the information the seller the and in in and is non–Big 4 private This to Big 4 the Big 4 with the to The of non–Big 4 private sellers have a impact on the one the to in the to the for a non–Big 4 private seller be as as a of that are for Big 4 private Big 4 are of is to a Big 4 to the for that the the to such the in or This is a important on the Big 4 of is that a of in to for in a lower poor information quality a reduce the in the to the and a Big 4 auditor are to and their are to a is This is especially for and as of a Big 4 one are to the of a Big 4 auditor are to to the the Big 4 in the to to This range Big 4 to the to an for to for a or the seller a at the of of in a and in a in the for the private seller is in of the of not be the are or to an to sell the such the seller not have to to the for engaging a Big 4 auditor and the of Big 4 sale the not have the to and a private seller to the lower information not private company a Big 4 our empirical models to for to auditor private have that are not Big 4 with with to a poor or Such are for to is that a of our Big 4 is with Big 4 that are not our a private seller in a Big 4 auditor and higher proceeds as our empirical our study not the with the of a Big 4 Such the higher Big 4 audit the as with in and to a the Big 4 of the Big 4 and higher with such as the of a or that with the of the Big 4 an is whether private sellers not a Big 4 auditor are value in of that are private company into be as and in in their to the of their Our research the existence of such to the of are their for This study a impact of Big 4 auditor choice on the sale proceeds of private in the as at least a explanation for the PCD, one to the information quality facing the buyer. This to for the PCD in the Officer The we are A private seller with value to and to a dollar value decrease in value to not a Big 4 auditor to and to we a not public and private and examines the impact of Big 4 on sale proceeds for auditor The dollar value decrease in value to not a Big 4 auditor with to and to Using approach, the value to not a Big 4 auditor is the Big 4 for public companies. with that Big 4 auditors provide and that the is and to in private companies with a Big 4 auditor are to have of as an and a companies are to have not a company with and the of is with the of a Big 4 a private company to a Big 4 auditor, our the in of not the of a Big 4 of the higher of a Big 4 auditor, information as as and we provide that Big 4 auditor choice consistent with the that Big 4 audit provide our multivariate that for of and our of the PCD and on the